Clinical Benefits of Piperacillin/Tazobactam versus a Combination of Ceftriaxone and Clindamycin in the Treatment of Early, Non-Ventilator, Hospital-Acquired Pneumonia in a Community-Based Hospital - Park GE; Ko JH; Ki HK (International Journal of General Medicine, 2020)
Ga Eun Park,1 Jae-Hoon Ko,2 Hyun Kyun Ki1 1Division of Infectious Disease, Konkuk University Medical Center, Konkuk University School of Medicine, Seoul, Korea; 2Division of Infectious Diseases, Department of Internal Medicine, Samsung Medical Center, Seoul, KoreaCorrespondence: Hyun Kyun KiDivision of Infectious Diseases, Konkuk University Medical Center, Konkuk University School of Medicine, 120-1, Neungdong-Ro, Gwangjin-gu, Seoul 05030, Republic of KoreaTel +82-2-2030-7546Email kihkdr@kuh.ac.krPurpose: There is an increasing prevalence of multidrug-resistant (MDR) organisms worldwide. Therefore, broad-spectrum antibiotics are recommended in the treatment of hospital-acquired pneumonia (HAP). However, it remains controversial whether patients with early onset, non-ventilator HAP (NV-HAP) should also be empirically treated with broad-spectrum antibiotics. We compared the clinical benefit of ceftriaxone plus clindamycin vs piperacillin/tazobactam as the initial empirical treatment of adults with early NV-HAP.Patients and Methods: Retrospective cohort study was conducted in adult patients who were diagnosed with early, NV-HAP between January 2013 and June 2017 at a community-based tertiary care hospital. Patients were eligible for inclusion if they had received empiric treatment with either ceftriaxone and clindamycin or piperacillin/tazobactam for at least 3 days. Patients with increased risk of MDR pathogens were excluded.Results: A total of 89 patients were treated with ceftriaxone and clindamycin, while 124 received piperacillin/tazobactam. There were no significant differences between the two antibiotic groups with regard to median age, sex, or risk of pneumonia. The 30-day all-cause mortality did not differ significantly between the ceftriaxone plus clindamycin and piperacillin/tazobactam groups (4.5% vs 1.6%, P=0.202, respectively). However, in multivariate analysis, clinical failure was more frequent in the ceftriaxone plus clindamycin group than in the piperacillin/tazobactam group (HR 3.316; 95% CI, 1.589– 6918, P=0.001).Conclusion: Treatment with piperacillin/tazobactam was more effective than that with ceftriaxone plus clindamycin in patients with early NV-HAP. This study supports the recent treatment recommendations that patients with early NV-HAP should be treated empirically with broad-spectrum antibiotics.Keywords: empirical antibiotics, hospital-acquired infection, pneumonia, multiple drug resistance